2013
DOI: 10.1186/1472-6939-14-33
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues in research involving minority populations: the process and outcomes of protocol review by the Ethics Committee of the Faculty of Tropical Medicine, Mahidol University, Thailand

Abstract: BackgroundRecruiting minorities into research studies requires special attention, particularly when studies involve “extra-vulnerable” participants with multiple vulnerabilities, e.g., pregnant women, the fetuses/neonates of ethnic minorities, children in refugee camps, or cross-border migrants. This study retrospectively analyzed submissions to the Ethics Committee of the Faculty of Tropical Medicine (FTM-EC) in Thailand. Issues related to the process and outcomes of proposal review, and the main issues for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 24 publications
5
12
0
1
Order By: Relevance
“…Inadequately described risks of study procedures have been reported to be one of the most common reasons why RECs request clarifications or demand amendments to research protocols and participant information sheets ( Adams et al, 2013 ; Dal-Re et al, 2004 ; Lopez-Parra et al, 2012 ; Happo et al, 2017 ), and our present findings are in line with these observations. However, there is still limited knowledge as to why researchers appear to focus on the presentation of certain potential study procedures risks more than others.…”
Section: Research Agendasupporting
confidence: 90%
See 1 more Smart Citation
“…Inadequately described risks of study procedures have been reported to be one of the most common reasons why RECs request clarifications or demand amendments to research protocols and participant information sheets ( Adams et al, 2013 ; Dal-Re et al, 2004 ; Lopez-Parra et al, 2012 ; Happo et al, 2017 ), and our present findings are in line with these observations. However, there is still limited knowledge as to why researchers appear to focus on the presentation of certain potential study procedures risks more than others.…”
Section: Research Agendasupporting
confidence: 90%
“…If a study protocol does not provide sufficient information to the REC about the risks inherent in the proposed study, the risk assessment may be conducted subjectively or have to be based on intuition ( Resnik, 2017 ). Moreover, incomplete risk descriptions may also lead to a delayed handling of the application because the REC may need to ask for clarifications regarding the possible risks ( Adams et al, 2013 ; Resnik, 2017 ; Happo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research methodology is another issue discussed and explained to researchers. A previous study conducted by FTM-EC, regarding the approval or non-approval of studies involving minorities, reported that one reason for non-approval was unclear research methodology [58] . The IRB Metrics results also indicate that the importance of research methodology is not research design per se , but rather sample size, data and specimen collection, inclusion-exclusion criteria, and confidentiality and privacy.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation processes of RECs can be analysed through assessment of their decision documents. In this connection, study methods, such as selection and recruitment of subjects, along with statistics, have been reported to be the key subjects of queries made or amendments requested by RECs (Adams et al, 2013; Angell et al, 2008; Boyce et al, 2002; Bueno et al, 2009; Dal-Re et al, 1999; Kent, 1999; Lutz et al, 2012; Mansbach et al, 2007; Martín-Arribas et al, 2012; van Lent et al, 2014). Studies involving vulnerable groups, such as minors, often prompt certain queries (Adams et al, 2013; Lidz et al, 2012; Martín-Arribas et al, 2012).…”
Section: Introductionmentioning
confidence: 99%